Salmonella Typhi-Exposed Placentae: Chorionic Villi Histomorphology and Neonatal Birthweight - Patience B. Tetteh-Quarcoo; Joana Twasam; Kevin Kofi Adutwum-Ofosu; John Ahenkorah; Bismarck Afedo Hottor; Nicholas T. K. D. Dayie; Peter Ofori Appiah; Emmanuel Afutu; Fleischer C. N. Kotey; Emilia Asuquo Udofia; Nii Koney-Kwaku Koney; Benjamin Arko-Boham; et al. (Diseases)
Background: Salmonella infections impose a substantial global health burden, with an estimated 95.1 million cases occurring annually. Pregnant women exhibit a heightened vulnerability due to pregnancy-specific immune adaptations and dietary habits that increase their risk of Salmonella exposure, facilitating possible damage to the placental barrier. Despite this significant burden, Salmonella-associated placental pathology remains poorly understood, particularly its impact on foetal development through microstructural alterations. Aim: This study utilised stereology to assess histomorphological and functional alterations in term placentae of Salmonella Typhi-exposed placentae, compared to unexposed controls. Methods: A hospital-based case-control study was conducted in Ghana. Of 237 screened women, 62 placentae were selected for analysis, comprising 31 Salmonella-exposed cases (IgG/IgM-positive in placental and cord blood) and 31 gestational age-matched controls (IgG/IgM-negative). Placental tissues were processed for histology and stereology. Neonatal birthweights were also compared. Results: Stereological assessment revealed significantly higher mean volume densities of syncytial knots in the study group (0.4755 ± 0.04) compared to the controls (0.3342 ± 0.04, p = 0.0219). Syncytial denudation was increased in the study group (0.8113 ± 0.09) relative to the controls (0.1975 ± 0.08, p < 0.0001). Foetal capillary volume density was also significantly elevated in the study group (5.1010 ± 0.32) compared to the controls (3.562 ± 0.47, p < 0.0001). In contrast, intervillous space volume was significantly reduced in the study group (9.5810 ± 0.05) compared to the controls (11.593 ± 0.26, p = 0.0053). Neonates of exposed mothers showed a non-significant reduction in birthweight. Conclusion: Salmonella Typhi exposure in pregnancy induces subtle, yet significant alterations in placental architecture, compromising villous integrity and vascular organisation. Although birthweight may appear unaffected, the observed changes point to reduced placental efficiency and merit further research into their developmental consequences and long-term effects on babies.